A Passive Harmonic Tag for Humidity Sensing. (23rd July 2014) - Lazaro, Antonio; Villarino, Ramon; Girbau, David
Abstract : This paper describes a passive harmonic tag for radio frequency identification (RFID) and wireless sensor applications. The tag uses a dual polarized UHF patch antenna as an input antenna. One of the outputs is connected to a frequency doubler, which consists of a Schottky diode with its output connected to a patch tuned at twice the input frequency. The other output of the input antenna feeds a DC power harvested converter that drives an oscillator which modulates its output signal by controlling the bias point of the Schottky diode. The antenna's output is also used as a humidity sensor. To achieve this, the antenna is loaded with an interdigital capacitor with humidity-dependent capacitance. The antenna is consequently detuned when humidity varies, and therefore the second harmonic power is received. The tag is manufactured using standard fiberglass substrate. The basic theory of harmonic tag operation is described and compared with the standard backscattering approach. Experimental results with a proof of concept using commercial components are presented.